2020
DOI: 10.3390/nu12020453
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sodium Intake and Food Sources among Chinese Adults: Data from the CNNHS 2010–2012

Abstract: The present study was done to examine the status of dietary sodium intake and dietary sources of sodium among Chinese adults. Data were obtained from China National Nutrition and Health Surveillance (CNNHS) 2010-2012. All adults recruited in this study provided complete dietary data on three-day consecutive 24-h dietary recalls combining with the household weighing method. Sodium intake was adjusted for energy to 2000 kcal/day using the residual method. Average sodium intake was 5013 (95% Confidence Interval, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…The prevalence rate differences between males and females observed in this study align well with the data from other parts of China (Xue et al, 2018). Due to the acceleration of urbanization, improvement of living standards, and the heavy-flavored diet of the Northern population (i.e., due to excessive use of salt) (Fang et al, 2020), the Northern Chinese have a higher prevalence of hypertension compared to those in the South (Zhao et al, 2004). As the survey site is limited to the Northern region, the findings of the current study can only be generalized to Northern (Chinese) older adults.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence rate differences between males and females observed in this study align well with the data from other parts of China (Xue et al, 2018). Due to the acceleration of urbanization, improvement of living standards, and the heavy-flavored diet of the Northern population (i.e., due to excessive use of salt) (Fang et al, 2020), the Northern Chinese have a higher prevalence of hypertension compared to those in the South (Zhao et al, 2004). As the survey site is limited to the Northern region, the findings of the current study can only be generalized to Northern (Chinese) older adults.…”
Section: Discussionsupporting
confidence: 86%
“…A high consumption of dietary Na was observed with the Latin American individuals, but lower than the world average intake (4000 mg/d) (33) . Some gaps comparing to WHO recommendations might exist (34) . Discrepancies between high-income and low-and middle-income countries (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…canned and frozen items), in addition to the salt added to the home-based preparation. Therefore, measurements to limit and monitor salt and Na intake are needed (34) . Also, family-based strategies are needed to promote healthy eating and reduce intake of Na and other nutrients-to-limit in Latin America (35,36) .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that dietary sodium intake among children and adolescent is 4102 mg/day, which exceeded the maximum recommended amount set by WHO [ 29 ]. In China, the main source of dietary sodium was salt; a previous study reported that salt accounted for more than two-thirds (68.7%) of total dietary sodium intake [ 30 ]. Therefore, reducing salt intake is a key stratagem to prevent overconsumption of sodium intake.…”
Section: Discussionmentioning
confidence: 99%